2010
DOI: 10.1016/j.otsr.2010.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Deep venous thrombosis associated with acute hematogenous osteomyelitis in children

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 15 publications
3
34
0
3
Order By: Relevance
“…Other studies have also reported a significantly higher complication rates particularly DVT and pulmonary complications in patients with MRSA osteoerticular infections. 7,8,13,14 Early diagnosis and aggressive antibiotic and surgical treatment can prevent mortality and morbidity associated …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also reported a significantly higher complication rates particularly DVT and pulmonary complications in patients with MRSA osteoerticular infections. 7,8,13,14 Early diagnosis and aggressive antibiotic and surgical treatment can prevent mortality and morbidity associated …”
Section: Discussionmentioning
confidence: 99%
“…1,7 Studies have also shown that musculoskeletal infections by MRSA have a higher incidence of deep vein thrombosis (DVT) and septic pulmonary emboli. 8,9 To mitigate morbidity and mortality due to MRSA, it is imperative to establish the diagnosis by high index of clinical suspicion along with imaging and growing the infecting organism in culture, which promotes the prompt institution of appropriate antibiotic therapy early in the course of the disease. However, numerous studies have quoted a culture negativity rate ranging from 30 to 50 percent.…”
Section: E3mentioning
confidence: 99%
“…With the emergence of CA-MRSA, deep venous thrombosis (DVT) adjacent to the site of OM has been described by several groups (506)(507)(508)(509)(510). DVT with acute OM has been associated with MRSA (506, 508), PVL-positive strains of S. aureus (510), and USA300 in particular (507).…”
Section: Osteoarticular Infections In Childrenmentioning
confidence: 99%
“…Annual incidence is 0.06-0.07/10,000 compared to 2-7/10,000 in adults (Lachambre et al, 2005). The incidence in association with acute osteomyelitis, however, is increasing and is present in around 9% of paediatric cases with osteomyelitis (Bouchoucha et al, 2010). Such patients with DVT (Figure 4) are more likely to be infected with MRSA.…”
Section: Venous Thromboembolismmentioning
confidence: 99%
“…Surgery is likewise more likely to be required for abscess drainage in these patients (Hollmig et al, 2007, Bouchoucha et al, 2010). …”
Section: Venous Thromboembolismmentioning
confidence: 99%